INTEGRATED LEARNING IN A MODERN SCHOOL IN THE CONTEXT OF DISTANCE EDUCATION - Horbatiuk, Oksana; Polishchuk, Svitlana; Kuchynska, Iryna; Blashkova, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The article is aimed at defining the concept of integrated learning and features of the implementation of this educational technology in modern general education institutions. In defining the key concept, the mechanisms of integration between the basic disciplines, which are appropriate for the use of integrated learning in the modern school, are considered. It is noted that integration can be carried out by two key mechanisms, each of which is aimed at the perception of pupils of the surrounding world as a whole, regardless of which aspect of science is its knowledge.The article reveals the essence of the integrated approach to education, its significance and impact on changing the structure of a particular subject, which is an important element in improving the effectiveness of the educational process. In addition, the article describes in detail the action of mechanisms in the implementation of the basics of an integrated lesson, as well as the content and operation of didactic principles for implementing an integrated approach.The main research methods are: Analysis of literature sources, observation, survey, generalization and statistical analysis.The article focuses on identifying opportunities for introducing distance learning into Ukrainian education using an integrative approach.The main results of the study give grounds for asserting that the active and professional use of distance education opportunities by teachers will contribute to solving the educational problems that have arisen in modern Ukraine. These changes will help build new ways of development and prospects for Ukrainian educators, based on the relevance and widespread use of online education.The authors proposed their own definitions of the concepts "value orientations", "personal values", "value orientations of Ukrainian youth".